Enhanced cytotoxic effect of camptothecin nanosponges in anaplastic thyroid cancer cells in vitro and in vivo on orthotopic xenograft tumors. (1st January 2017) - Gigliotti, Casimiro Luca; Ferrara, Benedetta; Occhipinti, Sergio; Boggio, Elena; Barrera, Giuseppina; Pizzimenti, Stefania; Giovarelli, Mirella; Fantozzi, Roberto; Chiocchetti, Annalisa; Argenziano, Monica; Clemente, Nausicaa; Trotta, Francesco; et al.
Abstract: Anaplastic carcinoma of the thyroid (ATC) is a lethal human malignant cancer with median survival of 6 months. To date, no treatment has substantially changed its course, which makes urgent need for the development of novel drugs or novel formulations for drug delivery. Nanomedicine has enormous potential to improve the accuracy of cancer therapy by enhancing availability and stability, decreasing effective doses and reducing side effects of drugs. Camptothecin (CPT) is an inhibitor of DNA topoisomerase-I with several anticancer properties but has poor solubility and a high degradation rate. Previously, we reported that CPT encapsulated in β-cyclodextrin-nanosponges (CN-CPT) increased solubility, was protected from degradation and inhibited the growth of prostate tumor cells both in vitro and in vivo . The aim of this study was to extend that work by assessing the CN-CPT effectiveness on ATC both in vitro and in vivo . Results showed that CN-CPT significantly inhibited viability, clonogenic capacity and cell-cycle progression of ATC cell lines showing a faster and enhanced effect compared to free CPT. Moreover, CN-CPT inhibited tumor cell adhesion to vascular endothelial cells, migration, secretion of pro-angiogenic factors (IL-8 and VEGF-α), expression of β-PIX, belonging to the Rho family activators, and phosphorylation of the Erk1/2 MAPK. Finally, CN-CPT significantly inhibited the growth, the metastatization and the vascularization of orthotopic ATC xenografts in SCID/beige mice without apparent toxic effects in vivo . This work extends the previous insight showing that β-cyclodextrin-nanosponges are a promising tool for the treatment of ATC.